Penggunaan Tabel Diagram untuk Meningkatkan Pengetahuan Matematika Dasar Penjumlahan pada Kelas 1 SDN 173635 Parparean II, Kecamatan Porsea, Kabupaten Toba - Mira Kristiyanti Gea; Pagit Rehulina Br Tarigan; Anggie Tampubolon; Mico Crechen Jeremias Situmeang; Yogi Jonathan Siregar; Parsaoran Silalahi (Komunitas: Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2025)
The community service aims to improve the understanding of grade 1 students of SDN 173635 Parparean II on the concept of addition through the use of diagram tables 1-9. This service activity was carried out by KPPM students of HKBP Nommensen University Medan in Parparean II village, Porsea District, Toba Regency. The methods used in this service are observation and evaluation test. The results of the service showed that the use of diagrammatic tables improved students understanding of the concept of addition. Students stated that the use of diagrammatic tables helped them understand the material better. By looking at the numbers in the 1-9 table, they can easily follow the addition steps and understand the relationship between numbers. This shows that the visual aids such as diagrammatic tables are very effective in supporting the teaching and learning process, especially for basic mathematics concepts that are often a challenge for students and the use of this learning method also creates a more interesting and interactive classroom atmosphere. Through this service can make an important contribution in improving the quality of education. The use of table diagrams can be expanded in various school, so that they can understand how to implement this method into the learning process in the future.